Cryopreserved Fetal Liver Cells Immobilized in Macroporous Carriers Promote Liver Function Recovery After Injury With 2-Acetylaminefluorene - Gritsay, D. V.; Lebedinskiy, A. S.; Ochenashko, O. V.; Petrenko, Yu. A. (Problems of Cryobiology and Cryomedicine, 2024)
The effect of cryopreserved fetal liver cells immobilized in macroporous alginate scaffolds on liver injury degree in rats with model of liver failure developed by administration of 2-acetylaminofluorene with subsequent partial hepatectomy. It was shown that immobilized fetal liver cells accelerated recovery of spesific hepatic indices: serum albumin, total bilirubin content, aminotransferase activity. The results of this work indicate the positive effect of fetal liver cells seeded in macroporous scaffolds on course of liver failure and argue the availability of this approach for liver failure treatment.